Correlation Between Smoking Paradox and Heart Rhythm Outcomes in Patients With Coronary Artery Disease Receiving Percutaneous Coronary Intervention - Wu, Han-Ping; Jan, Sheng-Ling; Chang, Shih-Lin; Huang, Chia-Chen; Lin, Mao-Jen (Frontiers in Cardiovascular Medicine, 2022)
Background: The effect of smoking on short-term outcomes among patients with acute coronary syndrome (ACS) undergoing percutaneous coronary intervention (PCI) is controversial. However, little is known about the impact of smoking on long-term outcomes in patients with stable coronary artery disease (CAD) who receive PCI. Methods: A total of 2044 patients with stable CAD undergoing PCI were evaluated. They were divided into two groups according to smoking status (current smokers vs. non-smokers). Baseline characteristics, exposed risk factors, angiographic findings, and interventional strategies were assessed to compare the long-term clinical outcomes between groups. Predictors for myocardial infarction (MI), all-cause death, cardiovascular (CV) death, and repeated PCI procedures were also analyzed. Results: Compared with non-smokers, current smokers were younger and mostly male (both P <0.01). They also had a lower prevalence of chronic kidney disease (CKD) and diabetes (both P <0.01). Drugs including a P2Y12 receptor inhibitor of platelets (P2Y12 inhibitor), beta-blockers (BB), and statins were used more frequently in current smokers (P<0.01, P<0.01, P=0.04, respectively). Freedom from all-cause death and CV death was lower in the non-smoker group (P<0.001, P=0.003, respectively). After adjustment, logistic regression revealed smoking was a major predictor for all-cause death and repeated PCI procedure (hazard ratio[HR]: 1.71 and 1.46, respectively) Conclusions: Smoker’s paradox extends to long-term outcome in patients with stable CAD undergoing PCI, which is partially explained by differences in baseline characteristics. However, smoking strongly predicted all-cause mortality and repeated PCI procedures in patients with stable CAD undergoing PCI.